1979
DOI: 10.1139/x79-004
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient cycles in pine and their adaptation to poor soils

Abstract: Values for the various fluxes of nitrogen through the tree–soil system were calculated using models derived from measurements of rates of input, accumulation, and transfer in plots of 11-m-tall Pinusnigra var. maritima (Ait.) Melv. that were showing growth responses to varying rates of nitrogen fertilizer. As the result of continuing immobilization in trees and humus, growth of the unfertilized trees was declining and the trees were having to sacrifice older tissues to mobilize sufficient nitrogen for new grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(60 citation statements)
references
References 0 publications
3
53
0
2
Order By: Relevance
“…As the whole plant is composed of tissues of different ages, in which the nutrient contents are not evenly distributed, the lower accumulation of N, P, K and Mg, both on a dry mass basis and on a unit area basis, with increasing leaf age can be explained by the nutrient availability and the mobility within the trees (Miller et al 1979;Saur et al 2000;Zas and Serrada 2003). It has also been reported that the contents of these nutrients are generally highest in the actively growing parts of the trees (e.g., leaves) and lowest in the structural and not actively growing parts (e.g., stem wood) (Wang et al 1996;Wang and Klinka 1997;Laclau et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As the whole plant is composed of tissues of different ages, in which the nutrient contents are not evenly distributed, the lower accumulation of N, P, K and Mg, both on a dry mass basis and on a unit area basis, with increasing leaf age can be explained by the nutrient availability and the mobility within the trees (Miller et al 1979;Saur et al 2000;Zas and Serrada 2003). It has also been reported that the contents of these nutrients are generally highest in the actively growing parts of the trees (e.g., leaves) and lowest in the structural and not actively growing parts (e.g., stem wood) (Wang et al 1996;Wang and Klinka 1997;Laclau et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tbe Storage atid seasonal intertial cycling of nitrogen (N) bas been sbovvn to be importatit for tbe sustainable growtb of evergreen trees (Miller et al, 1979;Rapp, Leclerc & Lossaint, 1979;Millaid & Proe, 1992). In conifers, N is stored duritig tbe winter in needles and remobilized in tbe spring duritig tbe growtb of new foliage, as sbowti by N budget studies (Turner, 1977;Ericsson et al, 1985, Nambiar & Fife, 1987Heltnisaari, 1992a, b) and tbe use of ""N to quantify internal cycling directly (Millat-d & Pioe, 1992), Nitrogen budget studies bave sbowti tbat enbanced site fertility increases tbe capacity for ititertial cycling (Miller et al, 1979), tbrougb increasing needle mass atid so tbe capacity for N storage (Nambiar & Eife, 1987;Heltnisaari, 1992«), Eew studies bave considered tbe impact of nutrient supply oti tbe efficieticy of tbe processes of internal cyclitig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches showed that, lower accumulation of nutrients (N, P), both on a dry mass basis and on a unit area basis, with increasing leaf age, can be explained by the nutrient availability and the mobility within the trees (Miller et al 1979;Saur et al 2000;Zas and Serrada 2003). Generally, contents of nutrients are higher in more actively growing parts of trees like leaves and fine roots (Wang et al 1996;Wang and Klinka 1997;Laclau et al 2001).…”
Section: Variation In Leaf Morphological and Stoichiometric Charactermentioning
confidence: 99%